Analysis of Air Pollution Levels in Lubuk Begalung Sub-District Padang - Agis Marwadi; Sanny Edinov (Postgraduate School, Universitas Negeri Padang, 2024)
Increasing development activities will also increase the risk of air pollution and environmental damage. This will cause damage to the structure and basic functions of ecosystems that support the lives of humans and other living creatures. Therefore, research regarding the analysis of air pollution levels is becoming increasingly important to carry out. This research aims to analyze the level of air pollution in Lubuk Begalung Sub-District, Padang City, and analyze the main sources of pollution that have an impact on the level of pollution. The research methods used in this research include direct observation and laboratory analysis to measure air quality and analyze the content of pollutants in it. Analysis of air pollution levels was carried out using descriptive statistical methods. Descriptive statistics were used to summarize the data and calculate the mean, median, and standard deviation values of the observed air quality parameters. The ISPU value obtained for the Total Suspended Particulate (TSP) parameter is 30.65, PM10 is 46.46, CO gas is 101.64, NO₂ gas is 49.2 and SO₂ gas is 50.86. From the analysis results, it can be seen It was concluded that the air quality in the Lubuk Begalung Sub-District area is still safe and has not polluted the air which is dangerous to human, animal, or plant health.